Evaluation of Functional Erythropoietin Receptor Status in Skeletal Muscle In Vivo: Acute and Prolonged Studies in Healthy Human Subjects - Christensen, Britt (Public Library of Science, 2012)
BACKGROUND: Erythropoietin receptors have been identified in human skeletal muscle tissue, but downstream signal transduction has not been investigated. We therefore studied in vivo effects of systemic erythropoietin exposure in human skeletal muscle. METHODOLOGY/PRINCIPAL FINDINGS: The protocols involved 1) acute effects of a single bolus injection of erythropoietin followed by consecutive muscle biopsies for 1–10 hours, and 2) a separate study with prolonged administration for 16 days with biopsies obtained before and after. The presence of erythropoietin receptors in muscle tissue as well as activation of Epo signalling pathways (STAT5, MAPK, Akt, IKK) were analysed by western blotting. Changes in muscle protein profiles after prolonged erythropoietin treatment were evaluated by 2D gel-electrophoresis and mass spectrometry. The presence of the erythropoietin receptor in skeletal muscle was confirmed, by the M20 but not the C20 antibody. However, no significant changes in phosphorylation of the Epo-R, STAT5, MAPK, Akt, Lyn, IKK, and p70S6K after erythropoietin administration were detected. The level of 8 protein spots were significantly altered after 16 days of rHuEpo treatment; one isoform of myosin light chain 3 and one of desmin/actin were decreased, while three isoforms of creatine kinase and two of glyceraldehyd-3-phosphate dehydrogenase were increased. CONCLUSIONS/SIGNIFICANCE: Acute exposure to recombinant human erythropoietin is not associated by detectable activation of the Epo-R or downstream signalling targets in human skeletal muscle in the resting situation, whereas more prolonged exposure induces significant changes in the skeletal muscle proteome. The absence of functional Epo receptor activity in human skeletal muscle indicates that the long-term effects are indirect and probably related to an increased oxidative capacity in this tissue.